Rested-state contractions and rest potentiation in spontaneously hypertensive rats - Pérez, Néstor Gustavo (1993)
To gain further insight into the excitation-contraction coupling mechanisms in hypertrophy, we studied rested-state contractions, rest decay curves, and rest potentiation under different experimental conditions using papillary muscles of spontaneously hypertensive rats (SHR) and age-matched normotensive Wistar and Wistar-Kyoto (WKY) rats. Under constant stimulation at 1.1 Hz, contractility and relaxation were not significantly different in hypertensive when compared with normotensive animals. Rested-state contraction (the first beat after a rest interval of 15 minutes) increased to 159.2 ± 23% and 123.5 ± 7.5% of prerest values in Wistar and WKY rats, respectively, whereas in SHR it did not differ from prerest values (92.8 ± 9.8%). Ryanodine, used to preferentially inhibit sarcoplasmic reticulum function, eliminated the differences in rested-state contractions observed between hypertensive and normotensive rats. Maximal rest potentiation (the first beat after a rest interval of 1 minute) was also significantly higher in Wistar and WKY rats than in SHR. These differences persisted at low extracellular Na⁺, when Ca2+ efflux via the Na⁺-Ca2+ exchanger was inhibited. Rest decay curves (the decay in contractility from maximal rest potentiation to rested-state contraction) showed a similar pattern in the three rat strains. The results suggest that the altered inotropic responses of the SHR arise from an alteration in calcium handling by the sarcoplasmic reticulum. Experiments on saponin-skinned trabeculae indicated that fractional calcium release induced by caffeine was significantly reduced in the SHR. We conclude that the altered inotropic response observed in SHR may reflect a diminished release of calcium from the sarcoplasmic reticulum.